A Comparative Study of Perceived Satisfaction of Employees Regarding Performance Management System in Context of IT Organisations. (September 2014) - Mishra, Geeta
Performance Management System (PMS) has always been a key concern in HR process and has attracted significant attention from both academicians and practitioners. The study was conducted in IT organisations in India as the growth in the service sector in India has been led by the IT–ITES sector, contributing substantially to increase in GDP, employment and exports. The study aims at comparing the perceived satisfaction of employees across IT organisations and exploring the mechanism of PMS in the selected organisations under study. Findings of the study present interesting and significant insights into the mechanism of PMS in IT organisations and in understanding the differences in perceived satisfaction of employees across organisations.